Depth‐resolved surface coil MRS (DRESS)‐localized dynamic 31P‐MRS of the exercising human gastrocnemius muscle at 7 T1. (9th September 2014) - Valkovič, Ladislav; Chmelík, Marek; Just Kukurová, Ivica; Jakubová, Michaela; Kipfelsberger, Monika Christina; Krumpolec, Patrik; Tušek Jelenc, Marjeta; Bogner, Wolfgang; Meyerspeer, Martin; Ukropec, Jozef; Frollo, Ivan; Ukropcová, Barbara; et al.
<x xml:space="preserve">Abstract</x> Dynamic 31P‐MRS with sufficiently high temporal resolution enables the non‐invasive evaluation of oxidative muscle metabolism through the measurement of phosphocreatine (PCr) recovery after exercise. Recently, single‐voxel localized 31P‐MRS was compared with surface coil localization in a dynamic fashion, and was shown to provide higher anatomical and physiological specificity. However, the relatively long TE needed for the single‐voxel localization scheme with adiabatic pulses limits the quantification of J‐coupled spin systems [e.g. adenosine triphosphate (ATP)]. Therefore, the aim of this study was to evaluate depth‐resolved surface coil MRS (DRESS) as an alternative localization method capable of free induction decay (FID) acquisition for dynamic 31P‐MRS at 7 T. The localization performance of the DRESS sequence was tested in a phantom. Subsequently, two dynamic examinations of plantar flexions at 25% of maximum voluntary contraction were conducted in 10 volunteers, one examination with and one without spatial localization. The DRESS slab was positioned obliquely over the gastrocnemius medialis muscle, avoiding other calf muscles. Under the same load, significant differences in PCr signal drop (31.2 ± 16.0% versus 43.3 ± 23.4%), end exercise pH (7.06 ± 0.02 versus 6.96 ± 0.11), initial recovery rate (0.24 ± 0.13 mm/s versus 0.35 ± 0.18 mm/s) and maximum oxidative flux (0.41 ± 0.14 mm/s versus 0.54 ± 0.16 mm/s) were found between the non‐localized and DRESS‐localized data, respectively. Splitting of the inorganic phosphate (Pi) signal was observed in several non‐localized datasets, but in none of the DRESS‐localized datasets. Our results suggest that the application of the DRESS localization scheme yielded good spatial selection, and provided muscle‐specific insight into oxidative metabolism, even at a relatively low exercise load. In addition, the non‐echo‐based FID acquisition allowed for reliable detection of ATP resonances, and therefore calculation of the specific maximum oxidative flux, in the gastrocnemius medialis using standard assumptions about resting ATP concentration in skeletal muscle. Copyright © 2014 John Wiley & Sons, Ltd.